Republic of Mozambique : Joint Staff Assessment of the Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The report focuses on the social sectors, agriculture, and governance. However, the report fails to highlight the importance of tackling decisively certain structural reforms that are critical to achieving the poverty reduction objectives of sustaining growth and reducing poverty. The composition of spending is evaluated, and then, it is compared with actual expenditure. Despite these advances, the efficiency of the education system in Mozambique is still low. The involvement of domestic and foreign partners will be taken into account in the planning process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet